A Critical Response to Heidi C. Giannini - Barnes, Philip (Journal of religious ethics, 2018)
In a recent article in this journal, Heidi Giannini (2017) has argued that the Christian doctrines of love and of hope require Christians to endorse universal, unconditional forgiveness, understood in terms of the renunciation of negative reactive attitudes. She also addresses criticisms of this interpretation. It is argued that Giannini has failed to provide a Christian justification for universal, unconditional forgiveness. Part of the problem is that she espouses a definition of forgiveness and an understanding of the nature of forgiveness that, as a result of neglecting the teaching of the New Testament, exhibits a number of incoherencies and theological weaknesses. Her account is also vulnerable to philosophical and moral criticisms of a serious nature.